2018
DOI: 10.1111/1440-1681.12915
|View full text |Cite
|
Sign up to set email alerts
|

Salmon calcitonin ameliorates migraine pain through modulation of CGRP release and dural mast cell degranulation in rats

Abstract: The exact mechanism of migraine pathophysiology still remains unclear due to the complex nature of migraine pain. Salmon calcitonin (SC) exhibits antinociceptive effects in the treatment of various pain conditions. In this study, we explored the mechanisms underlying the analgesic effect of salmon calcitonin on migrane pain using glyceryltrinitrate (GTN)-induced model of migraine and ex vivo meningeal preparations in rats. Rats were intraperitoneally administered saline, GTN (10 mg/kg), vehicle, saline + GTN, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 39 publications
2
44
0
Order By: Relevance
“…Finally, CGRP release in the meninges leads to vasodilation, mast cell degranulation, and neurogenic inflammation, mechanisms for migraine pain . Triptans prevent release of CGRP, interrupting this cascade …”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, CGRP release in the meninges leads to vasodilation, mast cell degranulation, and neurogenic inflammation, mechanisms for migraine pain . Triptans prevent release of CGRP, interrupting this cascade …”
Section: Pathophysiologymentioning
confidence: 99%
“…11 Finally, CGRP release in the meninges leads to vasodilation, mast cell degranulation, and neurogenic inflammation, mechanisms for migraine pain. [12][13][14][15] Triptans prevent release of CGRP, interrupting this cascade. 16,17 These and other basic science studies led to CGRP assuming the role of target for migraine translational research.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Nitroglycerin is a nitric oxide donor and regarded to exhibit its migraine-like effects via activation of nitric oxide synthase enzyme. We recently demonstrated that nitroglycerin treatment enhanced degranulation of mast cells in the meninges in a nitroglycerininduced rat model of migraine (7). Inducer effect of nitroglycerin on degranulation of mast cells in the meninges was also shown by another group previously (16).…”
Section: Resultsmentioning
confidence: 69%
“…Degranulation of the mast cells in the meninges contribute to migraine pain by leading to neurogenic inflammation, and activation and sensitization of the trigeminovascular system (8). Experimental studies have shown that increased number and enhanced degranulation of mast cells in the meninges contribute to the generation and maintenance of migraine pain (1,5,7). It has been demonstrated that mast cell mediators including serotonin, prostaglandin-I2, and histamine lead to the sensitization and activation of the meningeal nociceptors (9).…”
Section: öZmentioning
confidence: 99%
“…Normally activation of MCs is useful to establish homeostasis of body systems, but their over activation can chronically induce inflammatory responses such as in the case of asthma and arthritis (3). MCs participate in the inflammatory processes by releasing various pronociceptive, vasoactive and pro-inflammatory mediators from their granules through a process called degranulation (4). MCderived mediators such as serotonin, prostaglandin, histamine, tryptase, tumor necrosis factor-alpha (TNF-α), and interleukin (IL)-1β are able to trigger and enhance inflammatory reactions (5).…”
Section: Introductionmentioning
confidence: 99%